Factors affecting the feelings of safety among individuals with mild intellectual disabilities and severe challenging behaviour in residential care: A qualitative study of professional and service users' perspectives - Lokman, Suzanne; Bal, Roland; Didden, Robert; Embregts, Petri Jcm (Journal of intellectual disabilities, 2025)
This qualitative study focuses on what feeling safe means for people with mild intellectual disabilities and severe challenging behaviour, and which factors affect their sense of safety. Thematic analysis was used to analyse data collected during (1) ethnographic longitudinal research and (2) interviews and focus groups among professionals and service users. Feelings of safety were related to three main themes: (1) a physical environment that reduces risks and temptations; (2) a reliable, predictable, and supportive environment; and (3) an accepting environment that enables service users to establish a normal life. An analysis of which factors affect service users' sense of safety identified 20 themes (e.g. team climate) and 34 subthemes (e.g. interactions with other service users). Many of these factors were interconnected. Future research should explore what residential service organisations for people with intellectual disabilities and external actors (e.g. the police) can do to promote service users' feelings of safety.